REHABILITATION AND HEALTH-RELATED QUALITY OF LIFE AND FATIGUE IN PATIENTS WITH LUNG CANCER - EFFECTS OF EXERCISE - Morten Quist (Journal of Cancer Rehabilitation)
Lung cancer is a leading cause of cancer-related deaths worldwide, with symptoms like dyspnea, chronic cough, fatigue, and weight loss signifcantly affecting patients' health-related quality of life (HRQoL). Recent research highlights the critical role of rehabilitation, particularly exercise, in improving both physical and psychological outcomes in lung cancer patients. Exercise interventions not only enhance physical ftness but also help manage fatigue, improve muscle strength, and promote